PENEGAKAN HUKUM DALAM PENYIDIKAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Agus Setiawan (Jurnal Hukum, 2019)
The development of narcotic crime over time shows an increasing trend, so that enforcement should be improved. In law enforcement the narcotic crime, the police are law enforcement officers act as investigators. The problems discussed in this research is how the law enforcement narcotic crime in the jurisdiction of Police Semarang, the factors that affect law enforcement narcotic crime and any obstacles that arise in law enforcement narcotic crime in the jurisdiction of Police Semarang and effort overcome. The method used in this research is juridical sociological. The data used are primary data and secondary data. The method of data collection is done through field studies and literature, while the method of data analysis using qualitative analysis. The results show, that law enforcement narcotic crime at the stage of investigation carried out under the provisions of the Criminal Procedure Code. Factors that affect law enforcement narcotic crime is a factor of legislation, law enforcement apparatus, means or facility factors, community factors, and cultural factors. The obstacles that arise in law enforcement narcotic crime consist of internal resistance and external barriers.